Interior design a key element in discotheque industry in Metro Manila - Crisostomo, Ivy C.
The discotheque industry is a popular type of entertainment center. It is a multi-functional type of hospitality industry-one which is avenue for total entertainment, a venue fro dancing, for drinking or just meeting new acquaintances or just plainly for enjoyment. This has continuously expanded which was manifested by the large number of discos here at Metro Manila. There are a lot of factors which contributed to the success this industry. The kind of music played, the lighting system, ventilation, acoustics are some of the most important factors which should be considered. A dance floor should be enough to accommodate the disco goers and there should be an efficient and proper use of spaces. This should be planned well so as to avoid any traffic problem or accidents within the disco. The traffic flow of the employees and the clients should be observed in the design of such space. Moreover, due to the expansion of discos, each and every disco should create an image which would attract the people to go which will make the people go back to the said disco. Hence, the role of Interior Design is very important in this industry. It is through the help of an Interior Designer that a disco will be able to be distinct from the others.